Analisis Faktor-Faktor Perambahan Kawasan Hutan Lindung Egon Ilimedo RTK 107 (Studi Kasus di Desa Runut, Kecamatan Waigete, Kabupaten Sikka, Provinsi Nusa Tenggara Timur) - Theresia Luku Lea Leri; Nixon Rammang; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
This research was motivated by forest encroachment that occurred in the Egon Ilimedo RTK 107 protected forest area, Runut Village, Waigete District, Sikka Regency. This forest encroachment is a forest clearing activity with the aim of owning, controlling and utilizing forest products without looking at and paying attention to the main functions carried out by a forest area. Encroachment on the Egon Ilimedo RTK 107 protected forest area for agricultural activities. The aim of this research is to analyze the factors causing forest encroachment in the Egon Ilimedo RTK 107 Protected Forest Area, Runut Village, Waigete District, Sikka Regency with the type of research being a case study. The data collected consisted of primary and secondary data using a qualitative descriptive analysis method which was carried out in November 2023. The research respondents were 57 people consisting of 25 people who were squatters, 25 people who were not squatters and 7 people who were managing KPH Sikka (POLHUT) . Meanwhile, data analysis consists of data reduction, data presentation and drawing conclusions. The results of this research show that there are 6 factors that cause forest encroachment and 3 factors that most influence forest encroachment. Forest encroachment factors are: 1) Economic factors. 2) Soil fertility factors and limited land area. 3). Education and knowledge factors. 4) Tenure conflict factors. 5) Officer limitations factor. 6) implementation of legal sanctions. Meanwhile, the factors that most influence forest encroachment based on the frequency of mention of the same factors by different respondents include economic factors, soil fertility factors and limited land area and tenure conflict factors.